Highly Crosslinked Polyethylene Liners Have Negligible Wear at 10 Years: A Radiostereometric Analysis Study. Issue 3 (1st March 2022) - Campbell, David G.; Callary, Stuart A.
Abstract: Background: The introduction of crosslinked ultra-high molecular weight polyethylene (XLPE) acetabular liners has been very successful, with decreased wear and reduction in the rates of revision hip arthroplasties. XLPE is the preferred articulation for most surgeons; however, there are concerns about the long-term performance of XLPE liners created with different manufacturing processes, which may lead to time-dependent failure, including accelerated wear, after several years. Questions/purposes: (1) What is the amount and rate of wear during the first 10 years using radiostereometric analysis (RSA) measurements of patients who had THAs that included a second-generation XLPE bearing? (2) Does the rate of wear change after 5 years in situ? Methods: This is a brief follow-up of a previous RSA study. In that study, we prospectively enrolled 21 patients with osteoarthritis who underwent primary cementless THA with an XLPE acetabular liner (three cycles of 3Mrad annealed) and 32-mm articulation. That group represented 44% of the 48 THAs performed by the surgeon at the hospital where RSA was available; 16 had cemented hips, leaving 32 who were invited to participate in this study. Of those, 11 lived rurally and declined to participate, leaving 21 patients who were included in the initial study. Since then, three patients died, one developed dementia and could not participate, and one had revision THA for reasons other than wear, leaving 16 patients available for analysis at 10 years. Tantalum markers were inserted during surgery, and all patients had RSA radiographs taken at 1 week, 6 months, and 1, 2, 5, and 10 years postoperatively. Femoral head penetration into the acetabular component was measured with RSA, including bedding-in during the first year and annual wear thereafter. Results: The median medial, proximal, anterior, two-dimensional (2D), and three-dimensional (3D) wear rates between 1 and 10 years were -0.001, 0.004, -0.012, 0.000, and 0.002 mm/year, respectively. No patient in this cohort had a proximal or 2D wear rate greater than 0.025 mm/year. The median proximal wear rate between 5 and 10 years (0.002 mm/year) was not greater than wear at 1 to 5 years (0.004 mm/year). Conclusion: Femoral head penetration in this second-generation XLPE liner remained very low at 10 years and accelerated wear after 5 years in situ did not occur. Concerns about late-onset wear from oxidation of irradiated-annealed XLPE were not observed. The low level of wear remains encouraging for the future clinical performance of this material. Level of Evidence: Level II, therapeutic study.